Optimization of time scheduling planning with the precedence diagram method (PDM) on the drainage construction project - Siregar, Adde Currie; Noorkhayati, Noorkhayati; Yatnikasari, Santi; Aprisandi, Dasa; Agustina, Fitriyati (Jurnal Teknika, 2024)
Jalan Pemuda 1 is one of the city roads located in the Samarinda region that often experiences flooding. Therefore, the construction of adequate drainage is necessary to address this flood issue. The construction of this drainage system is expected to effectively solve the flooding problems in the area. The project utilizes precast U-ditches as part of the drainage, replacing the less effective manual methods. The project site frequently experiences tidal fluctuations from the Karangmumus River, which triggers the floods. The U-ditch Precast has dimensions of 240 cm width, 180 cm height, and 10 cm length. Additionally, this research aims to analyze the time optimization in drainage channel construction projects using the Precedence Diagram Method (PDM). The critical tasks in the construction of the drainage channel project are also analyzed using the PDM method. In this research phase, the author chose the Precedence Diagram Method (PDM) not only to clarify the tasks but also to improve project management efficiency and effectiveness to achieve optimal results. The advantage of the Precedence Diagram Method (PDM) is that it does not require dummy or additional activities, simplifies the project network creation, and the interdependence between activities can be arranged without adding new tasks. The accelerated tasks include mobility work, reduced from 7 days to 2 days, and demobilization, reduced from 7 days to 1 day. The occupational safety and health management system (K3) is reduced from 7 days to 2 days, and utility tasks (PDAM, PLN, Telkom) are reduced from 7 days to 2 days. The initial project scheduling indicates a duration of 210 days, but with optimization, the project is completed in 196 days, resulting in a time savings of 13 days. This study provides insights into the effectiveness of the PDM method in addressing critical challenges in construction projects, with implementation leading to more efficient planning and timely project completion.